Pengaturan Hak Waris bagi Anak yang Lahir dari Hubungan Inses dalam Perspektif Hukum Islam - Bertha Cahyadewi; Mega Dewi Ambarwati (Yayasan Penelitian dan Pengabdian Masyarakat Sisi Indonesia, 2025)
This study aims to analyze the regulation of inheritance rights for children born from incestuous relationships from the perspective of Islamic law. Incestuous relationships, which are explicitly prohibited in the Qur’an, Hadith, and national legislation, constitute violations of moral, social, and family law principles. However, the issue of civil rights for children born from such relationships, particularly regarding inheritance rights, remains a complex matter requiring further examination. This research employs a normative legal method using a statute approach and literature review. According to the Compilation of Islamic Law and the prevailing views of Islamic scholars (jumhur ulama), children born from incest are classified as children born out of wedlock (zina), possessing civil ties only to their mother and her family, and are therefore ineligible to inherit from their biological father. This provision aligns with the Islamic legal principle that a valid marriage is a prerequisite for establishing lineage (nasab) and inheritance rights. Nonetheless, it remains crucial to ensure the fulfillment of the child’s fundamental rights in accordance with principles of social justice and child protection. The findings of this study are expected to contribute to contemporary Islamic legal discourse on the protection of children in such challenging circumstances.